Explaining Foreign Exchange Market Puzzles - Miller, Norman (Washington, D.C. : International Monetary Fund, 1999)
The paper develops a flow model of the exchange rate with speculative capital flows integrated in a rigorous manner. The model is consistent with five foreign exchange market puzzles: (1) occasional discontinuous jumps in the exchange rate; (2) periodic short-term regimes of persistent appreciation/depreciation that can develop into a long swing; (3) the forward discount bias; (4) volatility clusters in the foreign exchange market that create conditional heteroskedasticity; and (5) the dual profitability of betting in the short run against any official foreign exchange intervention, and betting with the intervention in the long run.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet